The peculiar behaviour of burst oscillations in the accreting millisecond X-ray pulsar XTE J1814−338. Issue 1 (7th December 2021) - Cavecchi, Yuri; Patruno, Alessandro
ABSTRACT: Accreting millisecond X-ray pulsars (AMXPs) show burst oscillations during thermonuclear explosions of the accreted plasma that are markedly different from those observed in non-pulsating low-mass X-ray binaries. The AMXP XTE J1814−338 is known for having burst oscillations that are phase locked (constant phase difference) and coincident with the accretion-powered pulsations during all its thermonuclear bursts but the last one. In this work, we use a coherent timing analysis to investigate this phenomenon in more detail and with higher time resolution than was done in the past. We confirm that the burst oscillation phases are, on average, phase locked to the accretion-powered pulsations. However, they also display moderate (≲0.1 cycles) drifts during each individual burst, showing a repeating pattern that is consistently observed according to the thermonuclear burst phase (rise, peak, tail). Despite the existence of these drifting patterns, the burst oscillation phases somehow are able to average out at almost the exact position of the accretion-powered pulsations. We provide a kinematic description of the phenomenon and review the existing models in the literature. The phenomenon remains without a clear explanation, but we can place important constraints on the thermonuclear burst mechanism. In particular, the observations imply that the ignition point of the thermonuclear burst occurs close to the foot of the accretion column. We speculate that the burning fluid expands in a backward tilted accretion column trapped by the magnetic field, while at the same time the burning flame covers the surface.